Comparative analysis of hybrid nanofluids with Cattaneo-Christov heat flux model: A thermal case study - Hassan Waqas; Umar Farooq; Dong Liu; Muhammad Imran; Taseer Muhammad; Ali Saleh Alshomrani; Muhammad Umar (Case Studies in Thermal Engineering, 2022)
The hybrid nanofluids have higher heat transfer efficiency than nanofluids, which has expanded their applications to include electronic cooling, production, automobile, heat transfer, solar energy, heating elements, and biomedical. The current research aims to investigate the effects of Powell-Eyring hybrid nanofluid with slip boundary conditions, and the Cattaneo-Christov heat flux model over a moving surface. By applying the appropriate transformations, the governing boundary layer system is transformed into a dimensionless non-linear ODEs. These non-linear ODEs are computed numerically by using the Keller-Box method via computational tool MATLAB. Physical flow performance and numerical results of physical parameters are obtained by using the MATLAB tool. The researchers noted that hybrid nanofluid have a higher heat transfer rate than nanofluid. The consequences reveal that the velocity profile diminishes with an augmentation in a volumetric fraction of nanoparticles parameter, slip parameter, and porous medium parameter. Furthermore, an increase in thermal radiation parameter, volumetric fraction of nanoparticle parameter, Biot number, and thermal relaxation parameter enhance the temperature layer thickness. To the researchers' knowledge, no one has previously attempted to investigate the current challenge using a mass-based hybrid nanofluid framework. Furthermore, the problem's solution is novel. Indeed, the findings of this research are unique, and the numerical results have never been reported before. Furthermore, the researchers assumed that the findings of this study will be valuable in the development of a hot-wire anemometer or a shielded thermocouple for monitoring wind velocity, among other applications.